2020
DOI: 10.1016/j.esxm.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Information in YouTube Videos on Erectile Dysfunction

Abstract: Introduction Many patients seek information online including on social media. Aim To assess the quality of information regarding erectile dysfunction (ED) in YouTube videos. Methods We searched “erectile dysfunction” on YouTube in October 2019 and evaluated the first 100 videos in English sorted by relevance. Main Outcome Measure We recorded the user engagement, video producer, intended audience, and content. Video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 18 publications
8
65
1
3
Order By: Relevance
“…Similar to our study, Fode et al examined 100 YouTube videos about ED and reported that only 21 of these videos were uploaded directly by physicians. The authors reported that the quality of the examined videos was very good in two, good in 16, average in 21, poor in 35, and very poor in 18 [12]. Given that many previously conducted studies have reported health-related YouTube videos to be of low quality, our findings are not surprising [18][19][20].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Similar to our study, Fode et al examined 100 YouTube videos about ED and reported that only 21 of these videos were uploaded directly by physicians. The authors reported that the quality of the examined videos was very good in two, good in 16, average in 21, poor in 35, and very poor in 18 [12]. Given that many previously conducted studies have reported health-related YouTube videos to be of low quality, our findings are not surprising [18][19][20].…”
Section: Discussionsupporting
confidence: 50%
“…Recently, Fode et al evaluated YouTube content pertaining to ED. The authors assessed the videos using the Patient Education Materials Assessment Tool (PEMAT) and the Quality Criteria for Consumer Health Information (DISCERN) scales and reported that these videos were generally low quality and misleading [12]. In this study, we aimed to evaluate the most viewed videos on the treatment of ED in terms of content, accuracy, reliability, and quality.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies in the literature evaluating the reliability of YTVs related to men's health conditions such as male infertility, premature ejaculation, erectile dysfunction, benign prostatic hyperplasia treatment, and prostate cancer that also found that most YTVs related to the evaluated subject are unacceptable as a patient education resource. 12 , 14 , 15 , 16 For example, Loeb et al found that there is widespread dissemination of misinformation about prostate cancer on YouTube and that less reliable videos had increased user engagement. 12 However, the present study is one of the only studies to show that there is reliable information on YouTube and that it could be acceptable to use as a patient education resource if patients are directed to videos featuring board-certified physicians.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that 28% of 92 videos containing medical information contained misinformation. The results of their multivariate regression analysis revealed that all the parameters of videos uploaded by medical institutions had a statistically significant effect on DISCERN rating (30). In our study, the PEMAT score differed according to the upload source of the videos.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, in the study conducted by Fode et al, it was emphasized that there was no barrier and/or restriction when uploading content to websites, especially in the field of health. In the same study, the authors observed that the majority of the videos had a DISCERN score of 3 or less (30). In a study by Huang et al, there was no difference in the median number of viewers and viewer interaction according to low or high DISCERN scores.…”
Section: Discussionmentioning
confidence: 83%